Potential value of Gleason score in predicting the benefit of cabazitaxel in metastatic castration-resistant prostate cancer. (June 2013) - Buonerba, Carlo; Pond, Gregory R; Sonpavde, Guru; Federico, Piera; Rescigno, Pasquale; Puglia, Livio; Bosso, Davide; Virtuoso, Antonella; Policastro, Tania; Izzo, Michela; Vaccaro, Luca; Ferro, Matteo; et al.
Aim: This study aimed to identify predictive/prognostic factors in castration-resistant prostate cancer patients treated with cabazitaxel.Patients & methods: Patients were enrolled from March 2011 to December 2011 in an international expanded access program. In January 2012, when cabazitaxel became commercially available, a prospective study was initiated at University Federico II of Naples and at Rionero in Vulture Hospital.Results: Forty-seven patients were enrolled in this study. Patients received a median of nine cycles of cabazitaxel. Median progression-free survival was 7.0 months (95% CI: 5.7–8.0). Seventeen patients were still alive at the time of the analysis, with a median overall survival of 14 months (95% CI: 11–16). At multivariate analysis, a higher Gleason score (≥8) appeared to be associated with prolonged progression-free survival (hazard ratio: 0.36; 95% CI: 0.18–0.72); however, the higher Gleason score showed no statistical impact on overall survival.Conclusion: We hypothesize that the Gleason score has the potential to be incorporated in the clinical decision-making process for definition of treatment strategy in docetaxel-pretreated castration-resistant prostate cancer patients. We encourage further experimentation in this setting.